A novel approach based on viscoelastic parameters for bridge health monitoring: A case study of Saigon bridge in Ho Chi Minh City – Vietnam. (July 2020) - Nguyen, Thao D.; Nguyen, Thanh Q.; Nhat, Tam N.; Nguyen-Xuan, H.; Ngo, Nhi K.
Highlights: A viscoelastic approach into structural damage detection and diagnosis is proposed. The present method exploits amplitude and frequency of vibration signals and determines their relation with mechanical parameters in detecting structural changes. Two new parameters namely elastic module ( E ) and viscous coefficient ( C0 ) are suggested. Abstract: This article addresses a novel approach to diagnose a structure's damage based on changes in the mechanical parameters of materials. Firstly, we integrate a viscoelastic model into structural damage detection and diagnosis. Accordingly, this model defines materials' mechanical characteristics via two parameters namely elastic module ( E ) and viscous coefficient ( C0 ). While Hooke's model is linear, the viscoelastic is non-linear, and therefore, it reflects real situation more precisely. Secondly, we exploit amplitude and frequency of vibration signals and determines their relation with mechanical parameters in detecting structural changes. Based on theoretical analysis and experimental results, our study reveals more effective and general than previous ones. The simultaneous monitoring of structural change using different parameters allow the research to collect more appropriate data compared to previous studies. The results derived from this research were adopted in monitoring health of Saigon bridge over the period of 15 years. Via more than 100 sensors permanently attached to the bridge, the measured signals enabled the evaluation of the structure's operation status. This experimental result shows suitability among the proposed theoretical approaches, and thereby forms a basis to forecast damages of complex structures.